St Thomas's sermon Puer Iesus: a neglected source for his understanding of teaching and learning1 - Boland, Vivian (New blackfriars, 2007)
There are a number of places in his works where Thomas Aquinas writes about teaching and learning. Following a summary account of his understanding of education, this paper presents and discusses a neglected source on these matters. The sermon Puer Iesus, probably preached in January 1271, contains thoughts on pedagogy that are, in the words of its Leonine editor, ‘original and of great interest’. The sermon offers a broad sketch of human development in which the adolescence of Christ, the ‘most excellent of teachers’, is appealed to as an inspiration and an example. It raises Christological and pedagogical questions and it is the latter that are considered here. Encouraging his student congregation to listen generously, enquire diligently, respond prudently and meditate attentively, Aquinas outlines for them a practical method of learning that is at once critical and contemplative.